When Conversion is Joy and Death Victory: Historical Foundations of the Doctrine of Perseverance - Henžel, Ján (Tyndale bulletin, 2003)
Once people become converted one of their major existential concerns will be whether and how will they persevere in their right standing with God. As this concern is as old as Christianity, it is illuminating to see the historical developments of the doctrine of perseverance. Foundations of the doctrine may be found in the writings of Aurelius Augustine. There are to be found the four distinguishing approaches to the doctrine of perseverance developed in the course of history: (1) perseverance is necessary for believers’ salvation and that it is a gift of God but they are uncertain whether this gift was given to them; (2) perseverance is necessary, God determines who perseveres and the believer may be certain of this gift; (3) perseverance is a necessary gift but God does not determine who perseveres and the believer is uncertain of his final state; (4) perseverance is necessary for obtaining final rewards but not for believers’ salvation.